Penerapan K3 Menggunakan HIRARC (Hazard Identification Risk Assessment and Risk Control) pada Perusahaan Konstruksi di Cilegon - Setiawan, Lucky; Rahmatullah, Asep; Muhammad, Irfan; Rini, Asih Setyo; Hanan, Siti; Pratama, Theo Raka Haris (Fakultas Teknik Universitas Tulang Bawang, 2024)
One of the companies in the Cilegon area engaged in the construction industry has a high level of work risk. This company is required to implement an Occupational Safety and Health program to prevent workplace accidents.